Interpreting 9/11: The Role of Language and Narrative in the Construction of â€œAmericanâ€ Identity - TALLMAN, CHAD (Jurnal Studi Pemerintahan, 2014)
Following the attacks on September 11, 2001 (thatkilled approximately three thousand people) theUnited States began waging war abroad, resulting inthe deaths of hundreds of thousands of civilians andpermanently displacing millions of innocent people.The interpretation of 9/11 as an act of war by the U.S.government and the mainstream news mediaprovided the pretext for military aggression,legitimating war and militarizationâ€”on the basis ofâ€œnational securityâ€. This produced conditions for theheroic-narrative of the savior-nation to emerge,expressing itself in the United Statesâ€™ â€œWar on Terrorâ€.The idea of the â€œWar on Terrorâ€ was introduced in theaftermath of a lingering national traumaâ€”in manyways generated by the government and themainstream news media. Its repetition allowed it tobecome physically embodied in the human brain, andthereby, orienting people toward nationalism and theuse of violence. This study places identity at thecenter of the problem, arguing that â€œAmericanâ€identity is dependent upon the existence of anenemy- other (negative identity). Drawing upondiscoveries in cognitive science and neurosciencepermits one to appreciate the role of language andnarrative in the construction of identity and theimplications it has for both war and peace. Combiningthis research with a philosophical and religiousanalysis of the United States captures a trend in theactions, thought, and beliefs that help form theâ€œAmericanâ€ self and its relationship to violence.KEYWORDS: militarization, nationalism, heroicnarrative,language, identity